قياس مفهوم الوظائف التنفيذية متعدد الأبعاد لدى طلبة قسم التربية الرياضية في كلية التربية الأساسية - النعيمي, مهند محمد عبد الستار (Sulaimani Journal for Humanities, 2018)
The concept of executive functions is wide use variables in psychological and educational sciences. It is a multidimensional concept concerned with measuring the mental and cognitive skill set such as conceptual fluency (Figural Fluency) and thinking strategies (Strategies of Thinking) mental rotation (Mental Rotation) this concept is measured by testing five points (-point Test 5 )which is a computerized test of the Vienna test system examination and psychological diagnosis and current search target reformation:- 1- measure the multidimensional concept of executive Function (Figural Fluency- strategies of thinking-mental rotation) to a sample of students of physical education Department in the College of basic education at Diyala University. 2- know the differences in measuring a multidimensional executive function (Figural Fluency- strategies of thinking-mental rotation) among the students of physical education Department of basic education as a variable. 3- investigation of the relationship between variables link concept executive functions was multidimensional and relational implications to search sample calendar. Research sample consisted of 44 and a student of physical education students in the College of basic education 26 students and 18 a student using the bag of social sciences SPSS Research data has been processed the search results showed what becomes: 1- the levels of executive posts (Figural Fluency – thinking strategies-mental rotation) have a sample search was within the approved standards. 2- There are no significant differences in students moral Figural Fluency on as a variable. 3- There are no significant differences in students moral mental rotation as a variable. 4- There are no significant differences among students in moral thinking strategies as heterosexual. 5- There's a significant correlation function between Figural Fluency and variables of mental rotation. 6- There's a significant correlation function between Figural Fluency variables and thinking strategies. 7- There is a significant correlation between mental rotation variables function and thinking strategies.
Keywords: الوظتتتائف التنفيذيتتتتة Function Executive ال قتتتتة التصتتتورية Fluency Figural ااستتتترتاييييا التتتتتف اThinking of Strategies االتتداير العملتيRotation Mental التبتار النمتا اممستة Test Point5ل مناومتةالتبارا طيينا System Test Viennaل